Salt Intrusion as a Function of Estuary Length in Periodically Weakly Stratified Estuaries. Issue 15 (10th August 2022) - Wei, Xiaoyan; Williams, Megan E.; Brown, Jennifer M.; Thorne, Peter D.; Amoudry, Laurent O.
Abstract: Estuarine salt intrusion greatly threatens freshwater supply in surrounding lands. Physical barriers, which reduce the estuary length ( L ), are widely constructed to control salt intrusion. Yet, the role of L in salt intrusion remains unknown. Using a process‐based, idealized, semi‐analytical three‐dimensional model, we systematically investigate for the first time this unknown for tide‐dominated, periodically weakly stratified estuaries. Results show decreasing L significantly reduces salinities for short estuaries ( L < L w /4, with L w the dominant tidal wavelength), but not for long estuaries. Tidal pumping remains a key salt importer in most estuaries, regardless of L . However, substantial decreases in L relative to L w /4 can change the dominant landward salt importer from tidal pumping to horizontal diffusion. The latter, together with gravitational circulation, weakens responses of salt intrusion to changes in tidal and river forcing in short estuaries. This study highlights the importance of considering L to understanding and mitigating salt intrusion. Plain Language Summary: Salty seawater can enter rivers through estuaries, where rivers meet the sea, thus affecting the surrounding freshwater supply and the healthy functioning of estuarine ecosystems. To mitigate the adverse impact of salt intrusion under aggravating climate change and human activities, expensive salinity barriers are commonly built around the world. These barriers result in an abrupt change in the estuary length and can substantially affect estuarine salt intrusion. This study uses a simplified computer model to understand the dependency of salt intrusion on estuary length in estuaries with small top‐to‐bottom salinity differences. Our results show that estuary length substantially influences the salinity distribution and estuaries of different lengths can respond to changes in tides and river flow contrastingly. Our study highlights the importance of considering the impact of estuary length to effectively mitigate estuarine salt intrusion. Key Points: Estuary length strongly affects tidal propagation, residual circulation, and salt intrusion in periodically weakly stratified estuaries The dominant salt balance may change when substantially reducing estuary length Steady lateral shear dispersion can reduce responses of salt intrusion to forcing changes in short estuaries with weak stratification